Histone Deacetylases Inhibit the Snail2-Mediated EMT During Metastasis of Hepatocellular Carcinoma Cells - Hu, Yue; Nie, Qing; Dai, Mingrui; Chen, Fangfang; Wu, Hui (Frontiers in Cell and Developmental Biology, 2020)
Snail2 has important roles in the epithelial-to-mesenchymal transition (EMT) and tumor metastasis. However, the specific mechanisms involved in this process in hepatocellular carcinoma remain largely unknown. Here, we report that Snail2 is highly expressed during TGF-β–induced EMT in HL-7702 cells. Additionally, overexpression of Snail2 successfully promotes the migration and invasion of these cells, both in vitro and in a mouse model. Furthermore, our results show that HDAC1 and HDAC3 could specifically suppress the Snail2 gene promoter. Moreover, we found that the acetylation of H3K56 and H3K4, the targets of HDAC1 and HDAC3, was significantly reduced during the EMT process of liver HL-7702 cells. Thus, our results indicate that HDAC1 and HDAC3 epigenetically suppress the expression of Snail2 during the EMT of liver cells, revealing an opposing function of HDACs during the migration of malignant tumors.